Study of Telmisartan Versus Carvedilol for Prevention of Atrial Fibrillation Recurrence in Hypertensive Patients - K. China Venkanna, Dr. CH. Ananda Kumar, G. Rama Krishna, (Journal of Medical Biomedical and Applied Sciences, 2016)
Atrial remodeling, leading to atrial fibrillation (AF), is mediated by the reninâangiotensinâaldosterone system. Mild hypertensive outpatients (systolic/diastolic blood pressure 140â159/90â99 mmHg) in sinus rhythm who had experienced â¥ 1 electrocardiogram (ECG)-documented AF episode in the previous six months received randomly Telmisartan 80 mg/day or carvedilol 25 mg/day. Blood pressure and 24-hour ECG were monitored monthly for one year; patients were asked to report symptomatic AF episodes and to undergo an ECG as early as possible. One hundred and thirty-two patients completed the study (Telmisartan, n=70; carvedilol, n=62). Significantly fewer AF episodes were reported with Telmisartan versus carvedilol (14.3% vs. 37.1%; p<0.003). Left atrial diameter, assessed by echocardiography, was similar with Telmisartan and carvedilol (3.4Â±2.3 cm vs. 3.6Â±2.4 cm). At study end, both regimes significantly reduced mean left ventricular mass index, but the reduction obtained with Telmisartan was significantly greater than with carvedilol (117.8Â±10.7 vs. 124.7Â±14.5; p<0.0001). Mean blood pressure values were not significantly different between the groups (Telmisartan 154/97 to 123/75 mmHg; p<0.001; carvedilol 153/94 to 125/78 mmHg; p<0.001). Telmisartan was significantly more effective than carvedilol in preventing recurrent AF episodes in hypertensive AF patients, despite a similar lowering of blood pressure